Temporal-thermal enhancement of porous cooking burners - Hossein Soltanian; Mohammad Zabetian Targhi; Mehdi Maerefat (Scientific Reports)
Abstract Porous combustion has drawn vast attention over the last few decades leading to a variety of progressing applications particularly in industrial kitchens and household appliances that require time sensitive heating. The present study experimentally investigates the relationship between cooking duration and the thermal efficiency of a cooking pot heated on a porous burner providing a valuable insights into the effectiveness of the heating process in terms of both time and fuel consumption. To facilitate this investigation, a dedicated test bench is designed and constructed, equipped with thermometers and timer to effectively monitor the temporal/thermal behavior of the heating process. A mixed temporal/thermal metric is utilized to evaluate a premixed natural gas fueled porous burner with a typical cooking firing rate (FR) ranging from 800 to 2050 kW/m2. The results show that the optimal burner-pot distance is D = 1.5 cm, minimizing the load-averaged time to thermal efficiency (TT) to 19.5 s. Compared to D = 3 cm with FR = 800 kW/m2, thermal efficiency improves by 5.5%, heating time shortens by 120 s, and average firing rates save 51 s overall. An open conventional burner is also explored to show that by shifting towards temporally promoted porous burners, up to 2 minutes of cooking time could be saved.